Comparison of the In Vivo Efficacy of Cuban (Raydel®) and Chinese (BOC Science) Policosanol in Alleviating Dyslipidemia and Inflammation via Safeguarding Major Organs and Reproductive Health in Hyperlipidemic Zebrafish: A Twelve-Week Consumption Study - Kyung-Hyun Cho; Yunki Lee; Sang Hyuk Lee; Ji-Eun Kim; Ashutosh Bahuguna (MDPI AG, 2024)
Policosanol is a blend of long-chain aliphatic alcohols (LCAAs) and is well-known for several health-beneficial activities; however, the functionality of policosanol varied substantially based on the composition of LCAAs. In this study, two distinct policosanols, Raydel® (extracted from Cuban sugarcane wax) and BOC Sciences (extracted from Chinese sugarcane wax), were dietarily supplemented (0.1% w/w) for 12 weeks in hyperlipidemic zebrafish to examine their influence on the blood lipid profile and functionality of the liver, kidney, and reproductive organs. The results demonstrated a noteworthy impact of both policosanols on preventing high-cholesterol diet (HCD, 4% w/w)-induced dyslipidemia by decreasing total cholesterol (TC) and triglyceride (TG) levels in the plasma. However, compared to BOC Sciences, the Raydel® policosanol exhibited a significantly (p < 0.05) higher efficacy in reducing HCD-induced TC and TG levels. A substantial effect was observed exclusively with the Raydel® policosanol in mitigating HCD-impaired low-density-lipoprotein cholesterol (LDL-C) and high-density-lipoprotein cholesterol (HDL-C) levels. Hepatic histology and immunohistochemistry (IHC) analysis revealed the higher efficacy of Raydel® policosanol over BOC Sciences policosanol to prevent HCD-provoked fatty liver changes, cellular senescence, oxidative stress, and interleukin (IL)-6 production. Consistently, a significantly higher effect of Raydel® over BOC Sciences policosanol was observed on the protection of kidney, testis, and ovary morphology hampered by HCD consumption. In addition, Raydel® policosanol exhibited a notably stronger effect (~2-fold, p < 0.05) on the egg-laying ability of the zebrafish compared to policosanol from BOC Sciences. Furthermore, Raydel® policosanol plays a crucial role in improving embryo viability and mitigating developmental defects caused by the intake of an HCD. Conclusively, Raydel® policosanol displayed a substantially higher efficacy over BOC Sciences policosanol to revert HCD-induced dyslipidemia, the functionality of vital organs, and the reproductive health of zebrafish.